Company specific determinants of greenhouse gases disclosures. Issue 3 (4th November 2014) - Musa Mangena, Professor; Jia Liu, Dr; Chithambo, Lyton; Tauringana, Venancio
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the relationship between company-specific factors and the extent of greenhouse gas (GHG) disclosures. Design/methodology/approach – The study is based on a sample of 210 FTSE 350 companies and uses the disclosure index to quantify GHG disclosures made in the annual reports, sustainability reports and web sites in 2011. Ordinary least squares regression is employed to model the relationship between the company-specific factors and the extent of GHG disclosures. Findings – The results indicate that company size, gearing, financial slack and two industries (consumer services and industrials) are significantly associated with GHG disclosures while profitability, liquidity and capital expenditure are not. When the authors disaggregate GHG disclosures into qualitative and quantitative, the results suggest that the effect of some company factors differ depending on the type of GHG disclosures. Research limitations/implications – The study is cross-sectional. A longitudinal study is necessary to understand the dynamics of GHG disclosures as firms may change their disclosure policy as the importance of GHG increases. The results imply that policy makers need to take into account certain company-specific factors when formulating policy aimed at improving GHG disclosures. Originality/value – The results add evidence to the growing body of research focusing on the relationship between company-specific factors and GHG disclosure. The study also provides evidence that the effect of some company-specific factors on GHG disclosures differ depending on whether the GHG disclosures are quantitative or qualitative.